Universal Patterning for 2D Van der Waals Materials via Direct Optical Lithography. (21st August 2021) - Cho, Seong Rae; Ahn, Seonghun; Lee, Seung Hyung; Ha, Heonhak; Kim, Tae Soo; Jo, Min‐kyung; Song, Chanwoo; Im, Tae Hong; Rani, Pragya; Gyeon, Minseung; Cho, Kiwon; Song, Seungwoo; et al.
Abstract: Advanced patterning techniques are essential to pursue applications of 2D van der Waals (vdW) materials in electrical and optical devices. Here, the direct optical lithography (DOL) of vdW materials by single‐pulse irradiation of high‐power light through a photomask is reported. The DOL exhibits large‐scale patterning with a sub‐micrometer resolution and clean surface, which can be applied to various combinations of vdW materials and substrates. In addition, the thermal profile during DOL is investigated using the finite element method, and the ideal conditions of DOL according to the materials and substrates are determined. Abstract : A patterning method for van der Waals materials is introduced to pattern the materials via highly intensive light at multiple scales, high throughput, and high resolution. The method has scalability in types of materials and substrates and does not result in accompanying polymeric residues on the surface of the patterned materials unlike conventional photolithography. Simulations confirm that the intensive light allows high resolution patterning.